Study and Analysis Of Symbol Timing Offset Estimation Techniques in OFDM - Yashpreet (THAPAR UNIVERSITY, 2016)
In the last few years, number of mobile users/wireless users has been increased explosively all over the world. The demands for wireless communication network has been increased day by day and it cannot be satisfied with wired networks because it has been seen that wireless channels are more adulterated than wired networks. Orthogonal Frequency Division Multiplexing (OFDM) is a promising answer for this problem. It is a multi-carrier modulation and as well as a multiplexing technique proposed for 3G, 4G, LTE; a systems to support high data rate applications in fading environment. There are many problems linked with multi-carrier transmission like phase variations, timing offset, large peak to average power ratio (PAPR), frequency offset etc. in which Synchronization error(timing and frequency) of OFDM signal at the receiver is one of the major issues. This synchronization error destroys the orthogonality among subcarriers and hence cause inter-symbol interference (ISI) and inter-carrier interference (ICI) in OFDM symbol, which seriously degrades the overall system performance. There are two types of methods defined in literature used for the synchronization purpose. One is Data Aided (DA) method and another is Non Data Aided (NDA) method. In DA method, some training symbols or preambles are transmitted before the actual data symbols. At the receiver end start of training symbol is easily identified with the help of these training symbols using correlation methods. In Non Data Aided method blind technique is used with the help of cyclic prefix. In the thesis, a new estimation technique has been described which is based on the useful properties of Zad-off Chu (ZC) sequence. According to the proposed estimator, ZC sequence is employed as a training sequence whose frame format is based on IEEE 802.11a standard. In the proposed algorithm, Fractional Fourier Transform (FRFT) is mainly used and its cross-correlation property has been defined which is used further to obtain the exact estimation of symbol timing offset in the received signal. Simulation of various types of timing metrics has also been performed on MATLAB which are obtained using different methods, proposed in different papers and the performance of the proposed estimator has been calculated under HYPERLAN indoor channel-A using MATLAB and the results have been compared with the performance of estimator under AWGN using mathematical analysis.
Master of Engineering -Wireless Communication
Keywords: OFDM; SYMBOL TIMING OFFSET; FRFT; CFO